A linguagem poética na clínica fenomenológica existencial - Prado, Rafael Auler de Almeida (2013)
This study consists of a response given by us, researchers, to the uneasiness felt in our clinical psychology practice. Dialogue with our clients could be so spontaneous, unplanned and opened. That fact mobilized us to think about another way to understand the language in a clinical psychology comprehension, based on existential phenomenology. Language is fundamental to clinical psychology practice, no matter the theoretical conception of this practice. Having some psychological approaches more than others, their epistemological support by the scientific model of the natural sciences, their conceptions of language, therefore, refer in some way, to the representative aspect, according to which language would be a means of expression and / or communication. This conception, however, was not sufficient to clarify the clinical dialogue happened on the clinic. Client speeches seemed to go far beyond a mere means to express or communicate. Also our speech to our clients, seemed to us more like a "bring to light", or a "help to show" that the mere expression / communication. It was not clear to us, however, how could we understand language the way it happened in the clinical psychology practice, in existential phenomenological perspective, through dialogue. Among the studies that make a connection between the existential phenomenological thought of Heidegger and the clinical psychology, we found that many based on the existential analytic from Being and Time, but we did not find a study that explores the comprehension of language in Heidegger thought. At the time our concern emerged, the study of the philosophical and poetic works of Gaston Bachelard offered us another possible understanding of language through his notion of poetic imagination. We have also begun to research the language in work Heidegger´s later works. In this author´s existential phenomenological thought, however, language is understood from the conditions of existence, in its ontic-ontological articulation. In order to understand the language in a clinical psychology practice based on existential phenomenology, it was necessary to think about it in its articulation with other existential conditions of Heidegger's thought, which, like language, are also conditions for clinical psychology practice. This thesis aimed to take this issue forward. Gadamer´s philosophical hermeneutics helped us to recognize that "poetic language in clinical existential phenomenological" was a matter that has challenged us, clamored for answer. Hermeneutics guided the way we build our thesis. Consisting of four articles, the first one explain our presupposition of clinical psychology practice, based on existential phenomenological analytic of being-there from Being and Time. The second clarifies our understanding of poetic language. In it, we present the understanding of language to Heidegger, throughout his work, and approach the notion of poetic imagination of Bachelard. In the third article, we underline our methodological approach. In it, besides characterizing Gadamer's philosophical hermeneutics, we present our instrument, field diaries - founded by the narrative conception of Walter Benjamin. They consist of narratives about how we were affected by our psychotherapy sessions. Through the diaries, we brought our clinical experience (where our question emerged from) to dialogue with our presuppositions about the clinical psychology based on existential phenomenology, and our presuppositions about poetic language. The comprehension of dialogue, which we refer, is given by Gadamer. Dialogue between the field diaries and theoretical studies, resulted in the fourth article. This article showed a comprehension of clinical psychology practice as an opportunity to let poetic speech flows. This kind of speech invites the client to get ownership of their experiences, and their conditions of existence, to a more appropriate way of being.